2009
DOI: 10.1007/978-1-59745-471-1_25
|View full text |Cite
|
Sign up to set email alerts
|

Systemic First-Line Phenotyping

Abstract: With the completion of the mouse genome sequence an essential task for biomedical sciences in the twenty-first century will be the generation and functional analysis of mouse models for every gene in the mammalian genome. More than 30,000 mutations in ES cells will be engineered and thousands of mouse disease models will become available over the coming years by the collaborative effort of the International Mouse Knockout Consortium. In order to realize the full value of the mouse models proper characterizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 137 publications
0
66
0
Order By: Relevance
“…1). Systemic phenotypic screening of these mice at the German Mouse Clinic (29,30) revealed that they were healthy and showed no significant phenotype under nonstimulated conditions (the data can be accessed at: http://www.europhenome.org/).…”
Section: Resultsmentioning
confidence: 99%
“…1). Systemic phenotypic screening of these mice at the German Mouse Clinic (29,30) revealed that they were healthy and showed no significant phenotype under nonstimulated conditions (the data can be accessed at: http://www.europhenome.org/).…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of total IgE plasma levels by ELISA (18) in ADAR2 KO mice at the age of 14 weeks revealed statistically significant differences in females between mutants and controls (p ϭ 0.012; ϩ183.2%; Fig. 2).…”
Section: Morphological and Histological Examination Of Adar2 Komentioning
confidence: 93%
“…In the immunology screen, leukocyte populations and antibody isotype levels in peripheral blood were measured by flow cytometry and Luminex bead array technology (18). No differences in leukocyte subsets, such as T cells (CD3…”
Section: Morphological and Histological Examination Of Adar2 Komentioning
confidence: 99%
“…Animals were subsequently shipped to the German Mouse Clinic (46,47) for additional analyses (16-month vehicle, n = 19; 16-month rapamycin, n = 20; 25-month vehicle, n = 12; 25-month rapamycin, n = 16; 34-month vehicle, n = 11; 34-month rapamycin, n = 16). Cohorts were analyzed separately, each side by side with a group of young adult (3-6 months old) male C57BL/6J Rj mice (Janvier) kept on vehicle control diet (n = 10).…”
Section: Methodsmentioning
confidence: 99%
“…We used a modification of the SHIRPA screen (49) to assess 23 parameters related to neurological functions and general health as previously described (http://www.har.mrc.ac.uk/services/phenotyping/ neurology/shirpa.html) (46,47).…”
Section: Figure 10mentioning
confidence: 99%